2012
DOI: 10.1007/s12928-011-0094-8
|View full text |Cite
|
Sign up to set email alerts
|

Premenopausal woman with acute myocardial infarction caused by spontaneous coronary artery dissection and potential association with coronary vasospasm

Abstract: A 45-year-old premenopausal woman presented with acute myocardial infarction (MI). An intravascular ultrasound (IVUS) revealed that her distal right coronary artery was occluded by spontaneous coronary artery dissection (SCAD). She did not have any specific condition related to SCAD. At follow-up cardiac catheterization, an acetylcholine provocation test was applied to examine the etiology of SCAD, and definitive coronary vasospasm was induced with chest symptoms and significant electrocardiographic change. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…In general, SCAD occurs in younger women, especially at the peripartum period [3,4], but our three patients were not pregnant. Of these patients, two were diagnosed with coronary vasospastic angina, suggesting an association of coronary vasospasm and SCAD [8], and one had recurrent SCAD, as previously reported [3]. In this patient, recurrence of repeated SCAD has not been observed to date after concomitant pharmacological treatment with a calcium channel blocker.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In general, SCAD occurs in younger women, especially at the peripartum period [3,4], but our three patients were not pregnant. Of these patients, two were diagnosed with coronary vasospastic angina, suggesting an association of coronary vasospasm and SCAD [8], and one had recurrent SCAD, as previously reported [3]. In this patient, recurrence of repeated SCAD has not been observed to date after concomitant pharmacological treatment with a calcium channel blocker.…”
Section: Discussionsupporting
confidence: 65%
“…Ten days after emergency CAG, we performed pre-discharge follow-up CAG again and confirmed recovery of antegrade coronary flow at the distal LCX with repair of SCAD. At that point, administration of a calcium channel blocker was initiated because of the potential coexistence of SCAD and coronary vasospasm, which has been reported as a pathogenic cause of SCAD [8]. Six months after discharge, follow-up CAG was performed and the ergonovine provocation test showed coronary vasospasm in the LAD and LCX.…”
Section: Casementioning
confidence: 99%
“…Indeed, more than 50% of stable patients with suspected angina undergoing CAG had angiographically nonobstructive coronary arteries that did not require revascularization [4,10]. In addition, despite the high prevalence of obstructive coronary artery disease (CAD) in acute myocardial infarction (AMI), up to 13% of AMI patients had nonobstructive CAD (myocardial infarction with nonobstructive coronary arteries [MINOCA]) [6,7,[12][13][14]. This high prevalence of nonobstructive CAD has recently been reported not only in Japan but also in Western countries [6,10,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…SCAD is a rare but well-known cause of ACS and sudden cardiac death. Although a substantial proportion of SCAD cases have undetermined causes, some underlying conditions have been proposed, such as peripartum state among women, connective tissue disorders, coronary spasm, vasculitides, and intense exercise [2,[4][5][6][7][8]. Two institutes have recently reported a possible association between FMD and SCAD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the current investigations on the predilection of SCAD for young women without atherosclerosis, recent reports have focused on fibromuscular dysplasia (FMD) concomitant with SCAD [1,3]. These reports indicated that >50% of SCAD patients have FMD formation at the carotid, renal, and iliac arteries, as determined by angiography, suggesting that SCAD is associated with a predisposition of patients to coronary artery FMD, besides vasculitides, coronary spasm, and intense exercise, as reported in previous studies [4][5][6]. Therefore, a survey of the presence of noncoronary FMD as a causative factor of ACS concomitant with SCAD is important because of the associated high recurrence of coronary dissection among patients [3].…”
Section: Introductionmentioning
confidence: 89%